(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, we use Novel transform which has the form to solve a system of linear differential equations, while homogeneous or non-homogeneous system. Moreover, general formula of the set solution of systems of first and second order are derived.